2018
DOI: 10.3390/v10020080
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of HPV Epidemiology, Genomics and Mechanistic Studies of HPV-Mediated Carcinogenesis

Abstract: Of the ~60 human papillomavirus (HPV) genotypes that infect the cervicovaginal epithelium, only 12–13 “high-risk” types are well-established as causing cervical cancer, with HPV16 accounting for over half of all cases worldwide. While HPV16 is the most important carcinogenic type, variants of HPV16 can differ in their carcinogenicity by 10-fold or more in epidemiologic studies. Strong genotype-phenotype associations embedded in the small 8-kb HPV16 genome motivate molecular studies to understand the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 79 publications
1
86
1
10
Order By: Relevance
“…While there are no differences in E7 between A1 and D2 or D3, there are 3 amino acid differences in the E6 gene and functional studies indicate that these changes increase transforming ability (39). There are also a considerable number of amino acid differences (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) between A1 and D2 and D3 in other viral proteins, with the most variable E1, E2, and L1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are no differences in E7 between A1 and D2 or D3, there are 3 amino acid differences in the E6 gene and functional studies indicate that these changes increase transforming ability (39). There are also a considerable number of amino acid differences (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) between A1 and D2 and D3 in other viral proteins, with the most variable E1, E2, and L1.…”
Section: Discussionmentioning
confidence: 99%
“…HPV16 can be classified into four evolutionary-defined lineages (A, B, C, D), and 16 sublineages (A1-4, B1-4, C1-4, D1-4) (11), that vary in geographic distribution and disease risks (12)(13)(14)(15). HPV16 sublineages differ by 0.5-1% of the viral genome, and the A4, D2 and D3 sublineages are associated with 9-28-fold higher risk of cancer and 10-130-fold risk of adenocarcinoma (15).…”
Section: Introductionmentioning
confidence: 99%
“…HPV16 has coevolved with human kind, and its variants segregate robustly into a phylogenetic tree with four phylogenetic lineages (A, B, C and D) and 16 sub-lineages: A1-A3 variant (previously known as EUR), A4 variant (As), B1-B4 variant (AFR1), C1-C4 variant (AFR2), D1 variant (NA), D2 variant (AA2), D3 variant (AA1) and D4 variant [19,20]. Many studies reported that the carcinogenic capacity is different between sub-lineages, and the non-European lineages have stronger pathogenicity in developing cervix cancer in comparison with European lineages, such as the D3 variant (AA1) and A4 variant (As) [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…48 While cellular integration of viral genomic material is a means of propagation for families such as 49 4 of cancer) and eventual integration of HPV16 sequences into human DNA via double-strand break 71 (DSB) repair events [Winder et al, 2007], yielding unique integration signatures found in next- 72 generation sequencing (NGS) data from human carcinomas [Holmes et al, 2016]. 73 HPV16 sub-lineages (variants) via epidemiological and lab-based studies have been 74 reported to infer differing cancer risk [reviewed by Mirabello et al, 2018 and references within; 75 Clifford et al, 2019]. HPV16 variant designations were originally based on their geographical 76 region of origin and have since been updated to lineage (1.0 to 10.0% whole viral genome 77 sequence difference) and sub-lineage (0.5 to 1.0% difference) nomenclature.…”
mentioning
confidence: 99%